2016
DOI: 10.1002/jemt.22797
|View full text |Cite
|
Sign up to set email alerts
|

Anterograde and retrograde tracing with high molecular weight biotinylated dextran amine through thalamocortical and corticothalamic pathways

Abstract: Biotinylated dextran amine (BDA) has been used for neural pathway tracing in the central nervous system for many decades, in which high molecular weight BDA appeared to be transported predominantly in the anterograde direction and less in the retrograde direction. In the current study, we reexamined the properties of neural labeling with high molecular weight BDA through a reciprocal neural pathway between thalamus and somatosensory cortex. After injection of BDA into the ventral posteromedial nucleus of thala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Dextrans are cell impermeable hydrophilic polysaccharides that are often employed to monitor cell division, follow the movement of living cells, and evaluate the hydrodynamic characteristics of the cytoplasmic matrix. [51,52] Here, we were able to Similarly, Figure 7d-f shows dextran delivery, cell viability and merged image for 100 μm patterned area. The Calcein-AM image and merged image confirmed that cells are live after successful Dextran delivery.…”
Section: Dextran 3000 Mw Deliverymentioning
confidence: 69%
See 1 more Smart Citation
“…Dextrans are cell impermeable hydrophilic polysaccharides that are often employed to monitor cell division, follow the movement of living cells, and evaluate the hydrodynamic characteristics of the cytoplasmic matrix. [51,52] Here, we were able to Similarly, Figure 7d-f shows dextran delivery, cell viability and merged image for 100 μm patterned area. The Calcein-AM image and merged image confirmed that cells are live after successful Dextran delivery.…”
Section: Dextran 3000 Mw Deliverymentioning
confidence: 69%
“…Dextrans are cell impermeable hydrophilic polysaccharides that are often employed to monitor cell division, follow the movement of living cells, and evaluate the hydrodynamic characteristics of the cytoplasmic matrix. [ 51,52 ] Here, we were able to successfully deliver Tetramethylrhodamine‐labeled Dextran 3000 MW (Life Technologies) in a massively parallel manner utilizing the TMD device. The delivery efficiency for different concentration of Dextran 3000 was studied as shown in Figure S3b (Supporting Information) and was optimized at 30 µg mL −1 for further experiments.…”
Section: Resultsmentioning
confidence: 99%
“…With the advancements, scientists have developed various imaging techniques to trace neural networks using various chemical reagents. Some include dextran amines, Cholera β-Toxin subunit, tetanus toxin, and fluorogold. Dextran amines are lipophilic organic compounds with low toxicity and immunogenicity . These amines react with avidin–biotinylated horseradish peroxidase, followed by diaminobenzene as a substrate, and further analyzed by optical microscopy [Figure ].…”
Section: Optical Imaging Using Chemical and Genetically Modified Vira...mentioning
confidence: 99%
“…Despite the common perception that DAs are preferential anterograde tracers, many studies indicate bidirectional travel (Schmued et al, 1990;Fritzsch, 1993;Glover, 1995;Zhang et al, 2017), including the original description of their axonal transport by Glover et al (1986). Their retrograde capabilities have been exploited both for conventional tracing (Sivertsen et al, 2014(Sivertsen et al, , 2016Lunde et al, 2019) and for delivery of calcium-sensitive indicators for optical recording of neurons selected by axonal trajectory (O'Donovan et al, 1993;McPherson et al, 1997).…”
Section: Limitations Of Conventional Tracersmentioning
confidence: 99%
“…4. The direction of axonal transport is rarely exclusive, which complicates circuit analysis; the archetypal retrograde and anterograde tracers, CTb and BDA respectively, both label axons traveling in the "wrong" direction (Luppi et al, 1987;Schmued et al, 1990;Fritzsch, 1993;Glover, 1995;Angelucci et al, 1996;Noseda et al, 2010;Zhang et al, 2017). "…”
Section: Limitations Of Conventional Tracersmentioning
confidence: 99%